Advertisements as special instances of intersemiotic translation: an analysis of three multimedia campaigns - Simões, Elsa (2020)
The discursive nature of advertising, based on internal and external repetition, always demands some type of translation of meaning(s). In multimedia campaigns, the need for intersemiotic translation becomes even more pressing and perhaps more evident. It is essential to convey messages that must be perceived as having the same meaning, even though different media are being used, reaching audiences at diverse times and in different contexts. To demonstrate the different possibilities of the use of intersemiotic translations in multimedia advertising, two Portuguese campaigns and an international one are analysed, looking at how similarity effects are created that comply with 1) brevity demands required by limited amounts of space, time and audience’s attention span, 2) the need for message repetition to ensure memorability and 3) the need for originality and creativity required by this discursive genre.